Influence of natural climate curing treatment on corrosion activity of reinforced concrete - Egba, E.; Bakhary, N.; Ismail, Mohamed (2016)
Objective: This paper explained the experimental investigation conducted on reinforced concrete specimens to ascertain the effect of natural climate curing treatment on the corrosion activity. Methods/Statistical Analysis: Concrete specimens were prepared and given different curing treatments for 28 days. Sodium chloride was added to the concrete mix to accelerate corrosion. Two sets of the specimen were moisture cured for 3 days, then, one set out of the two was exposed to the sheltered environment, and the other set to the unsheltered environment to give the concrete a natural climate curing treatment. The specimens were subjected to different exposure conditions after the curing treatments. The half-cell potential and the nominal corrosion density were measured to study the effect of the natural climate curing treatment. Findings: The results revealed variation of the reinforced concrete corrosion process due to the natural climate curing treatment. There was a rapid shift of the trend of the corrosion activity for the specimens that underwent natural climate curing treatment from the fifth month of exposure duration; the corrosion activity in the specimens became higher than the specimens that were cured normal for 28 days in water at the six months of the exposure. The finding was attributed to the high rate of temperature and rainfall fluctuation within the tropical region, which caused massive imbalance in the early stage strength development of the concrete. The high temperature cum rainfall fluctuation rate disturbed the bonding of the concrete matrix which affected the reaction of the concrete to corrosion of the reinforcing steel bar eventually. Application/Improvement: The findings could find application in reinforced concrete durability analysis.